2016
DOI: 10.1002/2015jb012635
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the concentration of aluminum‐substituted hematite and goethite using diffuse reflectance spectrometry and rock magnetism: Feasibility and limitations

Abstract: Hematite and goethite in soils are often aluminum (Al) substituted, which can dramatically change their reflectance and magnetic properties and bias abundance estimates using diffuse reflectance spectroscopy (DRS) and magnetic techniques. In this study, synthetic Al‐substituted hematites and goethites and two Chinese loess/paleosol sequences were investigated to test the feasibility and limitations of estimating Al‐hematite and Al‐goethite concentration. When Al substitution is limited (Al/(Al + Fe) molar rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 69 publications
(147 reference statements)
1
26
0
1
Order By: Relevance
“…Compared with first derivative curves, the band location in second derivative curves is not influenced by other constituents or by the concentration of minerals in mixtures, and the second derivative is more suitable for natural samples (Liu et al, ). Besides natural samples, previous studies have investigated synthetic hematite/goethite samples using DRS and traditional rock magnetic methods and found that the DRS band amplitude in second order derivative curves is a relatively reliable concentration proxy for hematite and goethite (Hu et al, ; Jiang et al, ; Liu et al, ). In this study, we define Rel Hm+Gt to combine the concentration of hematite and goethite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with first derivative curves, the band location in second derivative curves is not influenced by other constituents or by the concentration of minerals in mixtures, and the second derivative is more suitable for natural samples (Liu et al, ). Besides natural samples, previous studies have investigated synthetic hematite/goethite samples using DRS and traditional rock magnetic methods and found that the DRS band amplitude in second order derivative curves is a relatively reliable concentration proxy for hematite and goethite (Hu et al, ; Jiang et al, ; Liu et al, ). In this study, we define Rel Hm+Gt to combine the concentration of hematite and goethite.…”
Section: Discussionmentioning
confidence: 99%
“…DRS technology has been used, for example, to identify a combination of hematite and goethite in eolian sediment fractions derived from northwest Africa (Balsam et al, ). Jiang et al () and Hu et al () demonstrated that the combination of DRS and magnetic methods should provide a more reliable approach for determining the concentration of antiferromagnetic minerals in sediments.…”
Section: Introductionmentioning
confidence: 99%
“…The HIRM, that is, “hard” IRM, is a method used to study the high‐coercivity minerals hematite and goethite (Bloemendal et al, ; Liu et al, ; Thompson & Oldfield, ). The approach of Hu et al () defines the HIRM as HIRM0.25em()FF,BF=()IRMFF+IRMBF÷2 …”
Section: Methodsmentioning
confidence: 99%
“…Diffuse reflectance spectroscopy (DRS) is used to interpret the types of magnetic minerals and their concentrations within the paleosols (Deaton & Balsam, ; Hu et al, ; Scheinost et al, ). This method determines sample composition through quantifying the interaction between visible light and the properties imparted to a soil/paleosol by Fe oxides.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation